Contrasting impacts of Kuroshio and Oyashio extension fronts on North Pacific storm track activity in spring - Na Xiao; Peilong Yu; Shiyao Chen; Xiaopei Lin; Min Yang; Minghao Yang (Climate Dynamics, 2026)

Precursorship between the Indian Ocean dipole and the following year ENSO in the CMIP6 simulations - Yue Zhong; Wenshi Lin; Dongliang Yuan; Tuantuan Zhang; Song Yang; Shuheng Lin; Wei Yu; Hanjie Fan (Climate Dynamics, 2026)

New relationship and mechanisms between Northeast China Cold Vortex and pre-flood season precipitation in South China under global warming - Baihui Guo; Yihe Fang; Yitong Lin; Yiqiu Yu; Chunyu Zhao; Yu Zhang; Yamin Hu; Mingsheng Wang (Climate Dynamics, 2025)

Impacts of model resolution on the simulation of sea-level variability by a global ocean-sea ice model - Yaqi Wang; Hailong Liu; Zipeng Yu; Pengfei Lin; Mengrong Ding (Climate Dynamics, 2025)

Wintertime atmospheric forcing of subtropical northeastern Pacific SST variability - Qi Shu; Yu Zhang; Jun-Chao Yang; Shengpeng Wang; Jian Shi; Xudong Wang; Xiaopei Lin (Climate Dynamics, 2024)

Positive feedback between the negative phase of interannual component of the Pacific Decadal Oscillation and La Niña - Hong-Shuo Tang; Yu Zhang; Yu Kosaka; Jun-Chao Yang; Qi Shu; Yi Liu; Xiaopei Lin (Climate Dynamics, 2024)

The warm Arctic-cold north american pattern in CanESM5 large ensemble simulations: Eurasian influence and uncertainty due to internal variability - Bin Yu; Hai Lin (Climate Dynamics, 2024)
This study examines the warm Arctic-cold North American pattern (WACNA) and its connection with the warm Arctic-cold Eurasia pattern (WACE) using ERA5 reanalysis and a 50-member ensemble of historical climate simulations produced by CanESM5, the Canadian model participated in CMIP6. The results indicate that a negative WACE-like pattern typically precedes a positive WACNA pattern by one month, and the presence of a negative Asian-Bering-North American (ABNA)-like circulation pattern connects Eurasia and North America, along with the Pacific-North American (PNA)-like pattern. The negative ABNA-like pattern can be attributed to anomalous heating in southern Siberia, which is associated with the negative WACE pattern and its featured Eurasian warming. The negative PNA-like pattern is influenced by negative SST anomalies in the tropical Pacific, resembling tropical ENSO variability. Anomalous temperature advection in the lower troposphere follows the circulation anomaly, which supports the formation of WACNA. Conversely, processes with circulation anomalies of opposite sign result in a negative WACNA pattern. The tropical ENSO variability does not significantly impact the WACNA pattern and its linkage with WACE. CanESM5 simulates the WACNA pattern and WACE-WACNA connection well, with some discrepancies in the magnitude of anomalies compared to ERA5 reanalysis. The uncertainty in the simulated WACNA pattern due to internal climate variability is dominated by two modes of inter-member variability: a southeast-northwest phase shift and a local variation in amplitude.

The benefits of high-resolution models in simulating the Kuroshio Extension and its long-term changes - Bo An; Yongqiang Yu; Helene Hewitt; Peili Wu; Kalli Furtado; Hailong Liu; Pengfei Lin; Yihua Luan; Kangjun Chen (Climate Dynamics, 2023)

Impact of the winter Arctic sea ice anomaly on the following summer tropical cyclone genesis frequency over the western North Pacific - Shangfeng Chen; Wen Chen; Bin Yu; Liang Wu; Lin Chen; Zhibo Li; Hasi Aru; Jingliang Huangfu (Climate Dynamics, 2023)

The dynamics of the equatorial Atlantic upwelling seasonal cycle under global warming and its potential impact on Pacific ENSO - Li-Chiao Wang; Thi Lan Dao; Yong-Fu Lin; Jia-Yuh Yu (Climate Dynamics, 2023)

A physical analysis of summertime North American heatwaves - Bin Yu; Hai Lin; Ruping Mo; Guilong Li (Climate Dynamics, 2023)
This study examines the dominant heatwave variability over North America (NA), extracted from an empirical orthogonal function (EOF) analysis of summertime monthly warm extreme index anomalies over 1959–2021. The principal mode features a dipole structure with a large area of anomaly over northwestern NA and an anomaly of opposite sign over the southern U.S. The corresponding principal component is associated with a large-scale atmospheric wave train extending from the North Pacific to North America (NP-NA) and a northeastward injection of moisture from the subtropical western Pacific towards western NA, which are key factors in supporting the NA heatwave variability. The NP-NA wave train can be systematically reinforced and supported by synoptic-scale eddies, and may also be forced by an anomalous convection over the tropical-subtropical western Pacific. Surface radiation heating directly contributes to surface temperature anomalies and is dominated by anomalous downwelling shortwave and longwave radiations. In association with a positive phase of the heatwave variability, the NP-NA wave train brings an anticyclonic anomaly over northern NA, leading to anomalous descent, reduced total cloud cover and below-normal precipitation and surface relative humidity over northern NA. Over northwestern NA, the anomalous subsidence causes air to warm through compression. Reduced cloud cover results in increased downward shortwave radiation that is a key contributor to surface radiation heating. In addition, increase in vertically integrated water vapour through the moisture injection from the North Pacific collocates with tropospheric warming. The atmosphere has more water vapor holding capability and acts as a greenhouse gas to absorb longwave radiation, leading to increased downward longwave radiation that is the second major contributor to surface radiation heating. Processes with circulation and surface radiation anomalies of opposite signs will likewise lead to the negative heatwave variability.

The linear behavior of the joint initial-boundary-value predictability of the climate system - Jianlin Yong; Shaoqing Zhang; Zhengyu Liu; Yang Gao; Lixin Wu; Jianping Li; Lv Lu; Yingjing Jiang; Xiaolin Yu; Mingkui Li; Haoran Zhao; Xiaopei Lin (Climate Dynamics, 2023)

Role of ocean dynamics in equatorial Pacific decadal variability - Yu Zhang; Shi-Yun Yu; Shang-Ping Xie; Dillon J. Amaya; Qihua Peng; Yu Kosaka; Xiaopei Lin; Jun-Chao Yang; Sarah M. Larson; Arthur J. Miller; Lei Fan (Climate Dynamics, 2022)

Tropical forcing of the circumglobal teleconnection pattern in boreal winter - Nicholas Soulard; Hai Lin; Jacques Derome; Bin Yu (Climate Dynamics, 2021)

The role of internal variability in climate change projections of North American surface air temperature and temperature extremes in CanESM2 large ensemble simulations - Bin Yu; Guilong Li; Shangfeng Chen; Hai Lin (Climate Dynamics, 2020)
Recent studies indicated that the internal climate variability plays an important role in various aspects of projected climate changes on regional and local scales. Here we present results of the spreads in projected trends of wintertime North American surface air temperature and extremes indices of warm and cold days over the next half-century, by analyzing a 50-member large ensemble of climate simulations conducted with CanESM2. CanESM2 simulations confirm the important role of internal variability in projected surface temperature trends as demonstrated in previous studies. Yet the spread in North American warming trends in CanESM2 is generally smaller than those obtained from CCSM3 and ECHAM5 large ensemble simulations. Despite this, large spreads in the climate means as well as climate change trends of North American temperature extremes are apparent in CanESM2, especially in the projected cold day trends. The ensemble mean of forced climate simulations reveals high risks of warm days over the western coast and northern Canada, as well as a weakening belt of cold days extending from Alaska to the northeast US. The individual ensemble members differ from the ensemble mean mainly in magnitude of the warm day trends, but depart considerably from the ensemble mean in spatial pattern and magnitude of the cold day trends. The signal-to-noise ratio pattern of the warm day trend resembles that of the surface air temperature trend, with stronger signals over northern Canada, Alaska, and the southwestern US than the midsection of the continent. The projected cold day patterns reveal strong signals over the southwestern US, northern Canada, and the northeastern US. In addition, the internally generated components of mean and extreme temperature trends exhibit spatial coherences over North America, and are comparable to their externally forced trends. The large-scale atmospheric circulation-induced temperature variability influences these trends. Overall, our results suggest that climate change trends of North American temperature extremes are likely very uncertain and need to be applied with caution.

A new DRP-4DVar-based coupled data assimilation system for decadal predictions using a fast online localization technique - Yujun He; Bin Wang; Wenyu Huang; Shiming Xu; Yong Wang; Li Liu; Lijuan Li; Juanjuan Liu; Yongqiang Yu; Yanluan Lin; Xiaomeng Huang; Yiran Peng (Climate Dynamics, 2020)

Modification of the wintertime Pacific–North American pattern related North American climate anomalies by the Asian–Bering–North American teleconnection - Bin Yu; Hai Lin (Climate Dynamics, 2019)

Reduced connection between the East Asian Summer Monsoon and Southern Hemisphere Circulation on interannual timescales under intense global warming - Tianlei Yu; Pinwen Guo; Jun Cheng; Aixue Hu; Pengfei Lin; Yongqiang Yu (Climate Dynamics, 2018)

Impact of atmospheric model resolution on simulation of ENSO feedback processes: a coupled model study - Lijuan Hua; Lin Chen; Xinyao Rong; Jingzhi Su; Lu Wang; Tim Li; Yongqiang Yu (Climate Dynamics, 2018)

A long-term tropical mesoscale convective systems dataset based on a novel objective automatic tracking algorithm - Xiaomeng Huang; Chenqi Hu; Xing Huang; Yang Chu; Yu-heng Tseng; Guang Jun Zhang; Yanluan Lin (Climate Dynamics, 2018)

The Asian–Bering–North American teleconnection: seasonality, maintenance, and climate impact on North America - Bin Yu; H. Lin; Z. W. Wu; W. J. Merryfield (Climate Dynamics, 2018)

A possible explanation for the divergent projection of ENSO amplitude change under global warming - Lin Chen; Tim Li; Yongqiang Yu; Swadhin K. Behera (Climate Dynamics, 2017)

Diagnosing the possible dynamics controlling Sahel precipitation in the short-range ensemble community atmospheric model hindcasts - Yu-heng Tseng; Yen-heng Lin; Min-hui Lo; Shu-chih Yang (Climate Dynamics, 2016)

Improved ENSO simulation from climate system model FGOALS-g1.0 to FGOALS-g2 - Lin Chen; Yongqiang Yu; Weipeng Zheng (Climate Dynamics, 2016)

Cause of severe droughts in Southwest China during 1951–2010 - Lin Feng; Tim Li; Weidong Yu (Climate Dynamics, 2014)

Indian Ocean variability in the CMIP5 multi-model ensemble: the zonal dipole mode - Lin Liu; Shang-Ping Xie; Xiao-Tong Zheng; Tim Li; Yan Du; Gang Huang; Wei-Dong Yu (Climate Dynamics, 2014)

Tropical/extratropical forcing on wintertime variability of the extratropical temperature and circulation - Bin Yu; Hai Lin (Climate Dynamics, 2013)